Rosie Revere, engineer - Beaty, Andrea; Roberts, David, 1970- (New York : Abrams Books for Young Readers, 2013)
A young aspiring engineer must first conquer her fear of failure.
Publisher's Weekly, July 2013.
3.7
K-3
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
AD780L
Keywords: Stories in rhyme; Engineers -- Fiction; Inventions -- Fiction; Failure (Psychology) -- Fiction; Perseverance (Ethics) -- Fiction; Perseverance -- Fiction; STEAM